Light and sex interplay: differential herbivore damage in sun and shade in dioecious Mercurialis perennis - Selaković, Sara D.; Stanisavljević, Nemanja S.; Vujić, Vukica D.; Rubinjoni, Luka Z.; Jovanović, Živko S.; Radović, Svetlana R.; Cvetković, Dragana D. (Archives of Biological Sciences, 2018)
Paper description: Light-induced changes in plant traits can result in light-differential herbivory. Usually plants in the shade are more damaged. In dioecious species plant sex can influence the outcome of plant-herbivore interactions, with male-biased herbivory suggested to be the rule. The simultaneous effects of light and plant sex on herbivory, plant morphological, defensive and nutritional quality traits were not previously explored. In shade tolerant species, herbivore pressure was higher at sun exposed sites. Light affected intersexual differences in defensive and nutritional quality traits. However these did not result in sex-biased herbivory. Plant morphological traits influenced herbivory rather than chemical defense. Abstract: Interactions between plants and herbivorous insects can be shaped by light environment, resulting in differential herbivory in sun and shade. In dioecious species, the combination of plant sex and light-induced changes in defense traits and nutritive value can alter the patterns of foliar damage. We explored the combined effects of light environment and plant sex on natural herbivore damage and plant traits in the dioecious understory forb Mercurialis perennis on Mt. Kopaonik (Serbia). The role of plant traits in predicting the extent of damage was examined as well. Male and female plants from contrasting light environments (shade vs. sun) were analyzed with respect to leaf damage, as well as plant morphological and biochemical traits (size, specific leaf area, carbon-based defensive compounds and nutritional quality). We found prominent differences in herbivore damage between sun and shade conditions, but not between the sexes. Plants from the sun-exposed site had a significantly larger leaf area removed. The specific leaf area co-varied with herbivore damage in an inverse fashion, while leaf nutritional value had a moderate effect. Contrasting light conditions influenced the patterns of intersexual differences in the contents of condensed tannins and soluble proteins, with females exhibiting higher trait values. We found that factors defining risk of consumption were related to plant morphological traits and nutritive value rather than to chemical defenses. https://doi.org/10.2298/ABS171207007S Received: December 7, 2017; Revised: January 16, 2018; Accepted: February 11, 2018; Published online: March 1, 2018 How to cite this article: Selaković SD, Stanisavljević NS, Vujić VD, Rubinjoni LZ, Jovanović ŽS, Radović SR, Cvetković DD. Light and sex interplay: differential herbivore damage in sun and shade in dioecious Mercurialis perennis. Arch Biol Sci. 2018;70(3):…